De novo mutations of \( ELANE\) gene in three Vietnamese patients with severe congenital neutropenia - Anh Linh, Duong; Van Anh, Nguyen Thi; Van Tung, Nguyen; Huy Hoang, Nguyen; Diem Ngoc, Ngo; Phuong Mai, Nguyen Thi; Manh Tien, Ngo; Thi Kim Lien, Nguyen (Academia Journal of Biology, 2022)
Severe congenital neutropenia (SCN) is a congenital condition in which granulocytes mature abnormally owing to a variety of genetic defects, resulting in immunodeficiency. Among the several genetic variations related to SCN, heterozygous mutations in the ELANE gene encoding neutrophil elastase account for approximately 60% of the genetic causes. Here, we present three patients from different Vietnamese families who were susceptible to infectious diseases such as lung abscesses, sepsis, cellulitis, and septicemia. Moreover, their hematological and immunological parameters were below the reference range. Whole exome sequencing (WES) analysis was performed in all cases harboring three previously described disease-causing mutations, including p.Arg103Pro, p.Trp156Arg, and p.Arg81Pro in the ELANE gene (NM_001972.4). These mutations were confirmed by the Sanger sequencing method in the patients, helping to identify de novo mutations in all cases. Our data increase more evidence for the function of ELANE in SCN, as well as raise awareness of this rare disease in the context of frequent infections in Vietnam.